PENGARUH OPINI AUDIT DAN TEMUAN AUDIT TERHADAP TINGKAT KORUPSI PEMERINTAH DAERAH DI INDONESIA (Studi Empiris pada Kabupaten dan Kota di Jawa Tengah Tahun 2015-2020) - Panji, Imam; Utomo, Dwi Cahyo (Diponegoro Journal of Accounting, 2023)
This study aims to test and find out the effect of audit opinions and audit findings on the level of corruption in local governments in Central Java Province. The research data used is secondary data from Central Java BPK Website, the annual audit report (LHP), and the Central Java High Court. This study uses multiple linear regression analysis to test the correlation between audit opinion and audit findings on the level of corruption. The test results individually prove that audit opinion has a negative effect on the level of corruption, and audit findings have no effect on the level of corruption in the district or city government in Central Java Province.